3,4-Methylenedioxymethamphetamine hepatotoxicity under the heat stress condition: novel insights from in vitro metabolomic studies - Araújo, Ana Margarida (2021)
Hyperthermia has been extensively reported as a life-threatening consequence of 3,4-methylenedioxymethamphetamine (MDMA, ecstasy) abuse. In this work, we used a sensitive untargeted metabolomic approach based on gas chromatography-mass spectrometry to evaluate the impact of hyperthermia on the hepatic metabolic changes caused by MDMA. For this purpose, primary mouse hepatocytes were exposed to subtoxic (LC01 and LC10) and toxic (LC30) concentrations of MDMA for 24 h, at 37 or 40.5 °C (simulating body temperature increase after MDMA consumption), and alterations on both intracellular metabolome and extracellular volatilome were evaluated. Multivariate analysis showed that metabolic patterns clearly discriminate MDMA treated cells from control cells, both in normothermic and hyperthermic conditions. The metabolic signature was found to be largely common to MDMA subtoxic and toxic concentrations, although with evident differences in the magnitude of response, with metabolic changes significantly more pronounced at 40.5 °C. Discriminant metabolites associated with MDMA-induced hepatotoxicity are mostly involved in the amino acid metabolism, aminoacyl tRNA biosynthesis, glutathione metabolism, tricarboxylic acid cycle, and pyruvate metabolism. Moreover, our metabolomic findings were corroborated by classical toxicity parameters, demonstrating the high sensitivity of this omic approach to assess molecular-level effects. Overall, this study indicates that MDMA triggers significant metabolic alterations on hepatic cells, even at low concentrations, that are clearly exacerbated at high temperatures. These findings provide new metabolic pieces to solve the puzzle of MDMA's hepatotoxicity mechanism and emphasize the increased risks of MDMA abuse due to the thermogenic action of the drug.